2020
DOI: 10.3390/ijms21197213
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Innate and Adaptive Immunity and Stabilization of Mast Cell Activation in Management of Infusion Related Reactions in Patients with Fabry Disease

Abstract: Fabry disease (FD) is an X-linked lysosomal disorder caused by mutations in GLA gene resulting in lack of or faulty α-galactosidase A (α-GalA) enzyme. Enzyme replacement therapy (ERT) with recombinant human α-GalA enzyme (agalsidase) is the standard treatment option for FD. Infusion-related reactions (IRRs), with symptoms ranging from rigors, to fever, pain, vomiting, angioedema and diarrhea, are often seen due to immune response against the exogenous enzyme. To elucidate the mechanisms causing the IRRs in FD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In this study the authors further demonstrated that circulating dendritic cells were drastically reduced during IARs, suggesting their possible sequestration to the sites of inflammation [39]. An increase in natural killer cells and a decrease in T cells was also observed [39]. In addition, cytokines IL-4, IL-8, and TNF-α showed a significant increase, indicating nonspecific degranulation of mast cells, indicating a crosstalk between immune cells resulting in IgE-independent mast-cell-specific allergic inflammation [39].…”
Section: Infusion-associated Reactionssupporting
confidence: 61%
See 4 more Smart Citations
“…In this study the authors further demonstrated that circulating dendritic cells were drastically reduced during IARs, suggesting their possible sequestration to the sites of inflammation [39]. An increase in natural killer cells and a decrease in T cells was also observed [39]. In addition, cytokines IL-4, IL-8, and TNF-α showed a significant increase, indicating nonspecific degranulation of mast cells, indicating a crosstalk between immune cells resulting in IgE-independent mast-cell-specific allergic inflammation [39].…”
Section: Infusion-associated Reactionssupporting
confidence: 61%
“…However, a recent study identified only 25% of patients with IARs with reduced C4 levels, suggesting that the primary cause for IARs is not complement-mediated cytotoxic hypersensitivity reactions [39]. In this study the authors further demonstrated that circulating dendritic cells were drastically reduced during IARs, suggesting their possible sequestration to the sites of inflammation [39]. An increase in natural killer cells and a decrease in T cells was also observed [39].…”
Section: Infusion-associated Reactionssupporting
confidence: 51%
See 3 more Smart Citations